THE IMPACT OF DIGITAL TOOLS ON NURSING STUDENTS’ CLINICAL PERFORMANCE: A MEDIATING ROLE OF COGNITIVE LOAD - Jiang, Yuan; Chen, Cuiping; Huang, Xiaomin; Zhang, Jian; Ding, Liyu (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The clinical performance of nursing students is a big problem in the era of modern technological advancement. With advancements in artificial intelligence and technology, clinical performance strategies with modern technology are required for nursing students. However, in the contemporary clinical environment of competition, a high level of performance is needed from nursing students. This research was conducted to investigate the impact of digital literacy level, instructor support for digital learning, and lack of technology anxiety on cognitive load and clinical performance. Furthermore, the study also investigated the direct impact of a lack of cognitive load on clinical performance. The mediating role of cognitive load in the relationship between digital literacy level, instructor support for digital learning, technology anxiety, and clinical performance was also investigated. A sample of 305 nursing students was collected from China using purposive sampling. This study used a Partial Least Squares – Structural Equation Model (PLS-SEM) to investigate the complex relationships presented in the framework. The study found that digital literacy level, instructor support for digital learning, and lack of technology anxiety have a significant impact on cognitive load and clinical performance. At the same time, the mediating role of lack of cognitive load between digital literacy level, instructor support for digital learning, lack of technology anxiety, and clinical performance was also accepted. The findings of this research provide new insights into clinical performance and nursing literature and recommend actionable practices for advancing the students’ clinical performance in China. JEL Classification Codes: C12, C20, C31.